Gender Narratives in Contemporary Prose Literature - Fadillah, Ega Nur (Journal of Literary Prose and Society, 2024)
This study examines how contemporary prose literature represents gender issues, traditional roles, and the complexities of gender identity in modern society. Through an analysis of selected works by both female writers and authors engaging with feminist and gender themes, the research investigates the ways in which prose serves as a medium to challenge, redefine, and reflect upon societal norms surrounding gender. This exploration highlights the narrative strategies employed to portray diverse gender experiences, emphasizing the tension between conventional expectations and individual identity formation. By focusing on narrative forms that question patriarchal structures and explore themes of empowerment, this study contributes to a deeper understanding of how literature can shape and respond to shifting discourses on gender in contemporary culture. The findings provide insight into the evolving portrayal of gender in prose and underscore the role of literature in promoting greater awareness and social change concerning gender equality.